Conformable fixture systems with flexure pins for improved workpiece holding - Craig, Oliver (2019)
The design of fixture systems for low stiffness freeform components is challenging. The tendency of thin components to deform under clamping, and vibrate during machining, are long-standing and persistent industrial problems. Excessive clamping-induced workpiece deformation can lead to poor dimensional accuracy, and weakening of the finished component due to residual stresses. Machining-induced vibration can affect the accuracy and surface finish of components, and also cause increased wear on the cutting tool, or even damage to the spindle bearings of the machine tool. Satisfactory fixturing of low stiffness components with high geometric complexity using conventional methods can be difficult and costly, due to the large numbers of clamps and/or dampers required to fully support and stabilise the workpiece. Fixturing of small components is particularly challenging, due to the lack of space for clamping and damping features. Furthermore, typical fixture systems cannot easily accommodate any manufacturing variability of blanks. These issues are particularly relevant to the machining of legacy components, where it is typically necessary to develop appropriate fixture solutions at low cost, and with short lead times.